Tertiary dentinogenesis with calcium hydroxide: A review of proposed mechanisms. (13th August 2012) - Sangwan, P.; Sangwan, A.; Duhan, J.; Rohilla, A.
Abstract Calcium hydroxide has been used extensively in dentistry for a century. Despite its widespread use as a pulp‐capping agent, its mechanisms of action still remain ambiguous. Understanding its modes of action will lead to a broader understanding of the mechanisms associated with induced dentinogenesis and help in optimizing the currently available agents to target specific regenerative processes to obtain the best possible clinical outcomes. A literature search relating to mechanisms of dentinogenesis of calcium hydroxide up to December 2011 was carried out using pubmed and MEDLINE database searches as well as manual searching of cross‐references from identified studies. Resulting suggestions regarding dentinogenic mechanisms of calcium hydroxide range from direct irritating action of the material to induction of release of biologically active molecules. The purpose of this article is to discuss various mechanisms through which calcium hydroxide may induce tertiary dentinogenesis in the light of observations made in included studies.